Procedural impact of advanced calcific plaque modification devices within percutaneous revascularization of chronic total occlusions ; coronary - Vadalà, Giuseppe; Mashayekhi, Kambis; Behnes, Michael; Ayoub, Mohamed; Gorgulu, Sevket; Werner, Gerald S.; Kalay, Nihat; Avran, Alexander; Goktekin, Omer; Garbo, Roberto; Jaroslaw, Wojcik; Zaczkiewicz, Myron; et al. (JACC Cardiovascular interventions, 2025)
Background - Significant calcifications within a coronary chronic total occlusion (CTO) increase procedural complexity and the risk for complications. Expert consensus documents recommend the use of advanced calcific plaque modification devices (ACPMDs) for calcified CTO percutaneous coronary intervention (PCI), whereas data on their procedural impact are limited. - Objectives - The aim of this study was to describe trends, settings, and outcomes of PCI of severely calcified CTO performed with and without ACPMDs. - Methods - Data from 15,329 CTO PCIs enrolled in the ERCTO (European Registry of Chronic Total Occlusion) between 2021 and 2023 were analyzed. On the basis of the presence of severe calcifications within the CTO, the study population was divided into 2 groups: nonsevere (n = 12,289) and severe (n = 3,040) calcium. Then, the severe group was divided into non-ACPMD (n = 2,253) and ACPMD (n = 787), according to the use of ACPMDs. - Results - Compared with the non-ACPMD group, the ACPMD group had higher rates of antegrade wiring (77.9% vs 49.2%; P < 0.001) and technical success (97.6% vs 79.1%; P = 0.001) and lower rates of periprocedural and in-hospital major adverse cardiac and cerebrovascular events (MACCE) (1.8% vs 3.5%; P = 0.001). A severe amount of calcium was independently associated with technical failure (OR: 3.13; 95% CI: 2.43-4.09; P < 0.001) but not with MACCE (OR: 0.88; 95% CI: 0.58-1.35; P = 0.15). Furthermore, extraplaque crossing was independently associated with MACCE (antegrade dissection and re-entry without retrograde contribution: OR: 3.12; 95% CI: 1.79-4.20; P < 0.001; antegrade dissection and re-entry with retrograde contribution: OR: 3.12; 95% CI: 1.67-4.11; P = 0.049; retrograde dissection and re-entry: OR: 1.90; 95% CI: 1.25-2.86; P = 0.002). - Conclusions - Applying ACPMDs in severely calcified CTO to PCI was associated with higher technical success and lower MACCE rates. The presence of severe coronary calcification on coronary angiography was a marker of clinical and procedural complexity and was associated with technical failure but not with MACCE.